Interculturality in English Teaching - A small study with Portuguese teachers - Leão, Ana Isabel dos Santos Ponce de (2018)
UNESCO and many other organisations worldwide have been working on approaches in education to develop tolerance, respect for cultural diversity and intercultural dialogue. Particularly, the Council of Europe has laid out guiding principles in several documents to promote intercultural competence, following Michael Byram’s and Geneviève Zarate’s efforts in integrating this important component in language education. This commitment on developing the intercultural competence has been so influential that many countries, e.g., Portugal, established the intercultural domain as a goal in the foreign language curricula. However, this commitment has been questioned by researchers worldwide, who consider that action is needed to effectively promote the intercultural competence. The research coordinated by Sercu, for example, suggests that foreign language teachers are willing to comply with an intercultural dimension, yet their profile is more in agreement with a traditional language teacher, rather than with a foreign language teacher, who proactively promotes the intercultural communicative competence. In this study, I propose to examine the teachers’ perceptions and beliefs about the intercultural competence in a cluster of schools in Portugal and compare these findings with Sercu’s study. Despite of a twelve-year gap between both, this study draws similar conclusions.